IMPROVING VOCABULARY MASTERY THROUGH LEARNING CIRCUIT MODEL IN THE ENGLISH SUBJECT AT THE FIFTH GRADE STUDENTS - Panji Maulana (English Education and Applied Linguistics Journal (EEAL Journal), 2020)
This study aims to improve students' vocabulary mastery in English subject by using the Circuit Learning Model for fifth grade students of SDN Margalaksana IV . This type of research is Classroom Action Research (CAR) which lasts for two cycles. Each cycle consists of planning, implementing, observing and evaluating actions, then reflecting. The subjects in this study were students in class IV C with a total of 27 students. The data in this study were obtained by using data collection techniques of written tests, observations, and oral tests. Based on the result of the research conducted, it showed that the pre-cycle reached an average grade of 45.8 with percentage of classical completeness of 22.2%. In cycle I, the average grade was 66.8 with the percentage of classical completeness of 55.6%. Then in cycle II, the average grade increased up to 85.4 with percentage of classical completeness of 81.5%. The conclusion of this study is that the Circuit Learning Model can improve the mastery of English vocabulary in fifth grade students at SDN Margalaksana IV Cilawu Garut.